(untitled) (Research, Society and Development, 2020)
The present article aims to analyze the way in which the elderly grandmothers who live in nursing homes in a public place in Santa Maria, Rio Grande do Sul, Brazil deal with their self-esteem, and how this interferes in your daily life. It was observed that the enclosure offers conditions of annihilation of the subjectivity of the inmates, there is no privacy, the rooms and personal items are shared, the rules and times are rigid, it is an environment where leisure prevails, coupled with permanent rest, corroborates for the psychic suffering of the inmates, leading to physical and mental indisposition. The research identified that there are several family and social situations that culminated in the search for a home for shelter of the elderly women who live there and who participated in the research, although a situation of family abandonment prevails as a common feature among the inmates. In this context, aiming to bring more joy to the elderly women living in an arid environment of affection, the researchers promoted an activity as a fantasy party in which a rich snack was served, accompanied by sweets and sodas, with songs from past times suggested by the inmates. As a result, the researchers provided the inmates with a festive and varied menu afternoon. The methodology used in the research was through an experience report coupled with a qualitative approach, since it does not present quantifiable data, but deals with the subjectivity of the participating group, in this case, the elderly residents of the home.